A stem of an arborescent lycopsid Sigillaria with attached rooting organs Stigmaria from the Pennsylvanian of the Donets Basin, eastern Ukraine - Vitaly Dernov; Halyna Anfimova (Geo&Bio)
The macroscopic remains of Carboniferous plants in the Donets Basin are represented by a variety of preservation types, including compressions, impressions, casts, as well as permineralised wood of gymnosperms preserved in alluvial and marine sandstones, permineralised organs of peat-forming plants in ‘coal balls’, etc. In contrast to other Carboniferous basins of the palaeotropical belt of Euramerica, the remains of arborescent lycopsid trunks preserved in situ are very rare in the Donets Basin. To date, only two such finds have been documented here, namely: a fragment of the Subsigillaria trunk found in the coal-bearing deposits of the Avilovka Formation (Upper Pennsylvanian) and a fragment of the Sigillaria trunk with attached rooting organs Stigmaria from the Gorlivka Formation (Middle Pennsylvanian). The latter trunk is currently on display at the National Museum of Natural History, National Academy of Sciences of Ukraine. Stigmaria represents root organs of several families of tree-like lycopsids, i.e. they are a classic form-genus. The remains of Stigmaria are among the most common Carboniferous fossils in the Donets Basin. Tree-like lycopsids, including representatives of the genera Lepidodendron, Sigillaria, Lepidophloios, and Asolanus, were among the dominants of wet forests growing within deltaic and alluvial lowlands, where peats were common. The taphonomic features of this trunk fragment indicate that Syringodendron, the preservation type of Sigillaria axes, may occur not only due to postmortem water transport of axes, but also due to the destructive effects of aggressive environmental agents on the surface layers of the stem, such as wind, moisture, activity of organisms, etc. The relatively large vertical angles of branching of Stigmaria rhizomorphs from the base of the trunk indicate their deep penetration into a substrate. This fact contradicts the assumptions of some experts about the subaerial or aerial location of at least some of the Stigmaria rhizomorphs. The fragment of Sigillaria stem with attached rhizomorphs Stigmaria is a valuable find, since the trunks of Pennsylvanian tree-like lycopsids are usually preserved without rooting organs.